First-principles study of superior hydrogen storage performance of Li-decorated Be2N6 monolayer. (31st July 2020) - Rahimi, Rezvan; Solimannejad, Mohammad
Abstract: The potential application of pristine Be2 N6 monolayer and Li-decorated Be2 N6 monolayer for hydrogen storage is researched by using periodic DFT calculations. Based on the obtained results, the Be2 N6 monolayer gets adsorb up to seven H2 molecules with an average binding energy of 0.099 eV/H2 which is close to the threshold energy of 0.1 eV required for practical applications. Decoration of the Be2 N6 monolayer with lithium atom signiﬁcantly improves the hydrogen storage ability of the desired monolayer compared to that of the pristine Be2 N6 monolayer. This can be attributed to the polarization of H2 molecules induced by the charge transfer from Li atoms to the Be2 N6 monolayer. Decoration of Be2 N6 monolayer with two lithium atoms gives a promising medium that can hold up to eight H2 molecules with average adsorption energy of 0.198 eV/H2 and hydrogen uptake capacities of 12.12 wt%. The obtained hydrogen uptake capacity of 2Li/Be2 N6 monolayer is much higher than the target set by the U.S. Department of Energy (5.5 wt% by 2020). Based on the van't Hoff equation, it is inferred that hydrogen desorption can occur at TD = 254 K for 2Li/Be2 N6 (8H2 ) system which is close to ambient conditions. This is a remarkable result indicating important practical applications of 2Li/Be2 N6 medium for hydrogen storage purposes. Highlights: H2 adsorption on the pristine and Li-decorated Be2 N6 monolayer is investigated. Adsorption energies are greater than the threshold energy of 0.1 eV. The hydrogen uptake capacity of 2Li/Be2 N6 is 12.12 wt%. The results of the present study are high as the goals specified by the USDOE.